In vitro antioxidant, anti-inflammatory, and anticancer activities of methanolic extract and its metabolites of whole plant Cardiospermum canescens Wall - Alekhya Ketha; Girija Sastry Vedula; A. V. S. Sastry (SpringerOpen, 2020)
Abstract Background Traditionally, the whole plant of Cardiospermum canescens has wide applications in the management of oxidative stress and inflammation in Africa and Asia. The present study investigated the antioxidant, anti-inflammatory, xanthine oxidase (XO) inhibitory, and anticancer activities of metabolites present in the crude methanolic extract of whole plant C. canescens (CCE). Results Chemical examination of CCE revealed the presence of six known compounds (1-6). From the results of in vitro studies, it can confirm that CCE exhibited notably inhibition of DPPH and superoxide free radicals, along with COX-1, COX-2, 5-LOX, and XO enzymes. Compounds 2 and 3 showed significant inhibition of DPPH and superoxide free radicals. Also, compound 2 exhibited good inhibition of COX-1 and COX-2 enzyme with IC50 of 87.0 and 88.0 μg/mL. Furthermore, CCE exhibited significant inhibition of 5-LOX and XO enzymes with IC50 of 42.5 and 56.0 μg/mL, respectively, while standard with IC50 of 42.5 and 56.0 μg/mL, respectively. Among the test series of cancer cell lines, compounds 2, 3, and CCE showed a significant percentage of cell growth lysis of DLD-1 with IC50 values of 52.5, 72.5, and 32.5 μg/mL, respectively. Besides, all the metabolites and CCE showed a very weak degree of specificity against NHME, indicates less toxicity to normal cells. Conclusion To conclude, the results of the present study indicated that the methanolic extract from the whole plant of C. canescens displayed antioxidant activity by inhibiting DPPH and superoxide free radicals; anti-inflammatory effects by regulating enzymes COX-1, COX-2, 5-LOX, and XO; and anticancer activity by inhibiting the growth of MCF-7, DLD-1, HeLa, and A549. These activities can link to natural active compounds 2 and 3. This study supports the traditional uses of the root of C. canescens. These data findings suggest that C. canescens can be a promising natural source of biological medicines for oxidative stress, inflammation, gout, and cancer.